Evolution of the fluid models for the solar coronal expansion - Alexander, Pedro (1993)
The question of just how the solar corona is expanding into the surrounding interplanetary region has been one of the most striking topics of space science since the late 1950's and it is still far from a definitive answer. The present script gives an overview of the observations and theories that led to the concept of that expansion and describes the subsequent models up to the present time. Finally, some of the open questions on the phenomenon are mentioned.